Lithuanian linguistic islands: research perspectives - Kardelis, Vytautas (Lietuvių kalba, 2015)
This article further discusses the topic of Lithuanian linguistic islands. It focuses on two particular aspects: a) synchronic aspect which is concerned with contemporary situation of the islands; b) diachronic aspect which focuses on the issue of the formation of Lithuanian islands. The article is of a discussable nature and some of the hypotheses that it raises are a result of an on-going work and thus are preliminary and they need to be tested and researched properly in the future. At this stage the key aims have been to raise and address those issues and questions that have only scarcely been addressed in extant linguistic literature. From the synchronic perspective, Lithuanian linguistic islands are classified according to the criterion of vitality. It is suggested that they be divided into three groups according to the level of their vitality: vital, endangered and dead. The analysis of the diachronic aspect, i.e. the history of the development of Lithuanian islands, the following questions of discussion are raised: 1) the question of the methodological approach with regard to Lithuanian islands. In dealing with it, it is suggested to consider not only the autochtonous model of the formation of islands but also examine the alochtonic (migrational) as well as mixed models. 2) The question of migration. The fact that people who spoke Slavic language varieties migrated to the ethnic Lithuanian lands in which Lithuanian was spoken is obvious. However, in theory, an opposite phenomenon might have been possible, i.e. it is possible that Lithuanians migrated to the areas of Slavic languages. In addition, the possibility of internal migration should not be underestimated either. In other words, it is possible that Lithuanians migrated in their own ethnic Lithuanian lands. 3) The question of dialectal situation. The main goal of the studies in this area is to establish dialectal identity of the linguistic islands. A theoretical assumption is made that in the ethnic Lithuanian lands in which Lithuanian islands formed, there might be dialectal units which used to be independent and which were not necessarily a relic of continental dialects. 4) The necessity of systematic linguistic studies. Lithuanian linguistic islands require systematic analysis and a synchronic research of Lithuanian islands’ phonological, morphological, syntactic and lexical structures. 5) Sociolinguistic question, especially from the perspective of historical sociolinguistics in which the key issue addressed is the interplay of the use of different languages and the situation of bilingualism. 6) Methodological concerns and the question of the necessity of complex studies. The main objective is for scholars of different fields to discuss, consider these points, to make use of the practical and methodological experience gained by foreign linguistics and to try to develop the research methodology of Lithuanian linguistic islands of a complex and synthetic character.
Keywords: linguistic islands; dialectal identity; historical sociolinguistics; migration; Gervėčiai; Lazūnai; Zietela